Enterramientos tardorromanos en la comarca del Alto Guadalentín (Lorca) - Martínez Rodríguez, Andrés (Antigüedad y Cristianismo, 1991)
The principal objetive of the investigations carried out in the late ancient necropolis of the Alto Guadalentin has been the search for new information related to the late ancient settlements in Lorca. The five cementeries studied are vinculated to rural settlements, of diferent entity but all sharing the same common denominator occupying a strategic location some distance from the valley. Due to the lack of funerary offerings, it is extremely dificult to establish an accurate chronology for these tombs. Analyses of the types of construction, due to their continuity in the period medieval, compel us to work within a wide time span, and has resulted in the fact that most of the time it is necesary to relate these cementeries to the nearest settlements.